Responding to the COVID-19 Pandemic: A New Surgical Patient Flow Utilizing the Preoperative Evaluation Clinic. (December 2020) - Pai, Sher-Lu; Irizarry-Alvarado, Joan M.; Pitruzzello, Nancy E.; Bosch, Wendelyn; Aniskevich, Stephen
During the coronavirus disease 2019 (COVID-19) pandemic, the study institution recognized the importance of providing preoperative COVID-19 testing and symptom screening to ensure patient safety. A multidisciplinary quality improvement team used Define, Measure, Analyze, Improve, and Control methodology to understand the issues, identify solutions, and streamline patient flow. The existing preoperative evaluation (POE) clinic was utilized as a centralized entity to provide COVID-19 testing, symptom screening, and infection prevention education in addition to routine preoperative medical optimization. With the new process, the percentage of patients with COVID-19 testing results returned before surgery increased from 10% to 100%. Of the 593 asymptomatic patients screened by the POE clinic, 2 were found to have positive results. These patients had their surgeries postponed until proper recovery. The study institution has extended this new process to all surgical patients, warranting facility readiness for the resumption of elective surgery.